2017
DOI: 10.1097/md.0000000000008171
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of robotic versus laparoscopic surgery for mid and low rectal cancer after neoadjuvant chemoradiation therapy and the effect of learning curve

Abstract: Randomized controlled trials have demonstrated that laparoscopic surgery for rectal cancer is safe and can accelerate recovery without compromising oncological outcomes. However, such a surgery is technically demanding, limiting its application in nonspecialized centers. The operational features of a robotic system may facilitate overcoming this limitation. Studies have reported the potential advantages of robotic surgery. However, only a few of them have featured the application of this surgery in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 38 publications
8
69
0
Order By: Relevance
“…A longer operative duration was the most consistent shortterm outcome in the series of meta-analysis and RCTs published on RRS for rectal cancer [8,9,[18][19][20][21][22][23][24], (Table 1). Jayne et al reported [8] that the mean operative duration was 37.5 min longer with RRS than with LRS performed by a surgeon experienced with a median of 91 LRS and 50 RRS cases.…”
Section: Operative Duration and Learning Curvementioning
confidence: 95%
See 1 more Smart Citation
“…A longer operative duration was the most consistent shortterm outcome in the series of meta-analysis and RCTs published on RRS for rectal cancer [8,9,[18][19][20][21][22][23][24], (Table 1). Jayne et al reported [8] that the mean operative duration was 37.5 min longer with RRS than with LRS performed by a surgeon experienced with a median of 91 LRS and 50 RRS cases.…”
Section: Operative Duration and Learning Curvementioning
confidence: 95%
“…In contrast, the learning curve for RRS ranged from 15 to 30 cases. Moreover, Huang et al [18] indicated that the learning curve for robotic surgery was shorter for patients with rectal cancer, and even for patients who principally exhibited more advanced disease after undergoing neoadjuvant chemoradiation therapy. Another significant aspect of the learning curve is related to whether it has an impact on the pathological outcomes for RRS.…”
Section: Operative Duration and Learning Curvementioning
confidence: 99%
“…101 Several studies have also compared outcomes of robotic-assisted resection to conventional laparoscopic resection. [102][103][104][105][106] Comparable results are generally seen between the approaches in conversion to open resection, TME quality, postoperative complications, and quality of life.…”
Section: Transabdominal Resectionmentioning
confidence: 99%
“…Use of the cumulative sum methodology to evaluate the learning process of RALS for rectal cancer has been reported. To date, nine studies have reported the learning curve of RALS for rectal cancer using the cumulative sum method, providing a range of 15–44 cases for the learning period . Conversely, previous studies that focused on the learning curve of laparoscopic rectal surgery estimated that approximately 40–90 cases are required to attain proficiency .…”
Section: Learning Curvementioning
confidence: 99%